Histopathologycal findings in the ovaries and uterus of albino female rats promoted by co-administration of synthetic steroids and nicotine - Camargo, Isabel Cristina Chericci [UNESP]; Leite, Gabriel Adan Araújo [UNESP]; Pinto, Tiago [UNESP]; Ribeiro-Paes, João Tadeu [UNESP] (Elsevier, 2014)
The use of anabolic androgenic steroids is often associated with the use of other substances, licit or not, such as nicotine present in the tobacco. The present study investigated for the first time the effects of co-administration of synthetic steroids and nicotine on the ovarian and uterine tissue and fertility of adult female rats. Animals were submitted to treatment groups (n = 16/group): nandrolone decanoate (ND; 7.5 mg/kg BW/week); testosterone mixture (T; 7.5 mg/kg BW/week); nicotine (N; 2.0 mg/kg BW/day), and co-administration of ND/N, T/N and ND/T/N. The control group received saline solution daily. The injections were administered subcutaneously for 30 consecutive days. Results demonstrated that all androgenized rats exhibited estral acyclicity and there was suppression of reproductive capacity due to notable ovarian and uterine histological changes. Treatments promoted decrease (p < 0.05) in the ovarian weight. Uterine weight increased (p < 0.05) in the T and T/N groups, in comparison to control group. ND or T co-administered or not to nicotine promoted intense follicular degeneration, with formation of cysts in the ovaries. High levels of circulating androgens in the ND/T/N group induced the presence of ovarian sex cord-stromal tumors of Sertoli cell pattern. Androgenized females presented endometrial changes characterized by papilliferous or pleated luminal epithelium, oedematous and hemorrhagic stroma and presence of gland cysts. In conclusion, the co-administration of three drugs promoted atypical morphological pattern on the ovaries and uterus of female rats.
Keywords: Nandrolone decanoate; Testosterone mixture; Nicotine; Ovary; Uterus; Histopathology; Rats